DISCLOSURE OF FORMATIVE ASSESSMENT PRACTICES IN THE MERDEKA CURRICULUM - Fitrah, Muh; Wajdi, Muhammad; Asrinan, Asrinan; Putri, Rukiana Novianti; Setiawan, Caly; Safroniou, Anastasia; Ruslan, Ruslan (Universitas Labuhanbatu, 2025)
Purpose – This research aims to analyze the experiences of middle school teachers in implementing formative assessment within the Merdeka Curriculum framework.Methodology—A qualitative case study was conducted from August to October at a Middle School in Bima City, West Nusa Tenggara, Indonesia. Ten Teacher Facilitators implementing the Merdeka Curriculum served as respondents. Data were collected through in-depth interviews, direct observations, and document analysis, then validated through triangulation and cross-checking. The data analysis included collection, condensation, display, and conclusion drawing.Findings – The findings indicate that teachers effectively utilized various formative assessment methods, including direct observation, quizzes, questionnaires, written tests, Q&A sessions, assignments, performance assessments, portfolios, and feedback. Feedback strategies addressed students' feelings, material reflections, and test evaluations. Students responded positively, showing acceptance, satisfaction, and increased motivation. The continuity of formative assessment improved learning activities and participation. Teachers employed engaging strategies such as feedback, self-evaluation, and peer assessment, while assessment data were utilized for result analysis, lesson planning, and differentiated learning. Despite challenges in question design, format analysis, and assessment selection, teachers recommended regular formative assessment implementation, enhanced student engagement, constructive feedback, professional competence improvement, responsiveness to student needs, and parental involvement.Significance – This study provides insights into the practical application of formative assessment in the Merdeka Curriculum, offering strategies to enhance teaching effectiveness and student engagement while addressing challenges faced by educators in resource-limited contexts. Keywords: Formative assessment, Merdeka curriculum, Teaching practices, Education.